(untitled) (Journal Of Educational and Psychological Researches, 2023)
The study aims to develop the awareness of the criteria for judging electronic educational materials among students of educational qualification at Dhofar University over spreading the Corona pandemic through a program based on mini-educational units. The study was applied to (18) students studying Teaching diploma at Dhofar University for the academic year 2020-2021, and their number. They were chosen intentionally. The study resulted in reaching a list of criteria for judging electronic educational materials, roughly (18) criteria in the selection themes and (15) criteria in the use theme. The level of awareness of the sample members with the criteria for selecting and using electronic educational materials and the effectiveness of the program in increasing awareness of students with standards recorded low levels. The study came out with a set of recommendations: holding training courses for students of the Teaching diploma and student teachers in the various disciplines of education through adopting the current criteria. Including these criteria through studying the educational teaching diploma and the bachelor of education. Adopting the current program in all disciplines in the department of education. Thus, we can make good use of it in light of the Corona pandemic.